2022
DOI: 10.1007/s00338-022-02220-3
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale biogeographic patterns are reflected in the genetic structure of a broadcast spawning stony coral

Abstract: Countries in the Western Indian Ocean (WIO) and along the Red Sea are particularly vulnerable to coral reef degradation, and understanding the degree of connectivity among coral reefs is a first step toward efficient conservation. The aim of this study is to investigate the genetic diversity, population structure and connectivity patterns of the broadcast spawning coral Acropora tenuis, first at a large scale comparing the Red Sea and the WIO, and second at a smaller scale comparing sites within the WIO. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
(102 reference statements)
1
7
1
Order By: Relevance
“…Third, genetic diversity within datasets followed a scaling relationship with area ( 18 ) that confirmed decreasing gene flow with increasing geographic distance, as observed in other Acropora populations ( Fig. S24 ) ( 19, 20 ).…”
supporting
confidence: 73%
“…Third, genetic diversity within datasets followed a scaling relationship with area ( 18 ) that confirmed decreasing gene flow with increasing geographic distance, as observed in other Acropora populations ( Fig. S24 ) ( 19, 20 ).…”
supporting
confidence: 73%
“…Our analyses group the entire Mozambique Channel region together at low numbers of clusters (supplementary materials, fig. S7), indicative of frequent larval dispersal across the basin, further supported by population genetics from a broadcasting coral (van der Ven et al, 2022). However, with finer granularity, it is clear that a (permeable) dispersal barrier exists across the Mozambique Channel (fig.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, no such barrier was identified by Spalding et al (2007), or other population genetic analyses (e.g. Souter and Grahn, 2008; van der Ven et al, 2022). Spalding et al (2007) instead identified an ecoregion boundary in northern Kenya.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given the vastness of coral reef ecosystems like the GBR, the number of reefs composing them, and the huge number of larvae released during spawning events, it is impossible to directly validate our models by tracking individual larvae in the water. Indirect validation of larvae dispersal based on genetic markers [51][52][53] is also not an option as the processes driving genetic differentiation take place on time scales of multiple generations 54 , where we only simulated one spawning event. The simulated hydrodynamics, which drive larval dispersal, has however been properly validated 20,38,47 .…”
Section: /16mentioning
confidence: 99%